HYPERACTIVE SYNDROME IN CHILDREN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The most common behavioral disorder is attention deficit hyperactivity disorder (ADHD) in children. The article presents an analysis of scientific works of both foreign and domestic researchers on the issue of ADHD in children of primary school age. The criteria for the primary assessment of the manifestations of hyperactivity and anxiety in a child are shown. Children with ADHD are characterized by irresponsible behavior, problems in relationships with peers and parents, people around them, and non-compliance with generally accepted rules. Therefore, timely diagnosis of the disorder and the development of comprehensive medical and psychological corrective measures are very important.